MARRIAGE SATISFACTION ON A COUPLE OF TUNGGU TUBANG IN THE SEMENDE TRADITION OF SOUTH SUMATRA - Yusafrida Rasyidin; Annisa Fitriani (AGENDA: Jurnal Analisis Gender dan Agama, 2021)
The purpose of this research is to find out how marriage satisfaction is to know what are the factors that influence marriage satisfaction in the waiting couple tubang in the traditional traditions of Semende, South Sumatra. This research uses a qualitative approach with a case study method, the data analysis technique used is thematic analysis by coding the results of the interview transcripts that have been made verbatim. The results showed that effective communication and cooperation play a role in marital satisfaction, effective communication can solve problems related to finance, family, parenting and sex. Whereas role cooperation in the family is an absolute requirement for family function and the openness of the couple to recognize and solve problems that arise to get the best solution.